How a container shipping company creates value in supply chain management from logistics perspective – a case study on Mediterranean Shipping Company Bangladesh LTD. - Monsur, Adnan Bin (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.